Penerapan smokless burn barrel untuk pengelolaan sampah ramah lingkungan di Desa Ploso Kabupaten Kediri - Dentina Nurhayati Elmi; Muhammad Budi Hidayat; Talitha Leila Arsanti; Qurrota A’yunin; Laela Dwi Lestari; Dimas Yasin Romli; M. Ubaidillah Ridwanulloh; Agus Miftakus Surur (CV Rezki Media, 2025)
Environmental management, particularly waste management, is one of the main challenges that requires serious attention. In communities, household waste and dry leaves are generally still disposed of through open burning, which has become a daily habit. This practice has the potential to cause various negative impacts on the environment, public health, and the quality of life of residents. This program aims to introduce the Smokeless Burn Barrel as an innovative solution for household waste management and burning. The activity was conducted in Ploso Village, Mojo District, Kediri Regency, utilizing a Participatory Action Research (PAR) approach that encompassed observation, problem identification, and action stages. The results of the implementation demonstrate that the use of the Smokeless Burn Barrel can accelerate the burning process, with an average time of 14.75 minutes, resulting in a 49.17% increase in efficiency compared to conventional methods. The combustion temperature also increased significantly, reaching an average of 351°C, representing a 63.94% increase, which resulted in a more complete combustion process with significantly less black and white smoke and minimal ash residue. Thus, the Smokeless Burn Barrel method has been proven effective in reducing the amount of residual waste, increasing energy efficiency during the combustion process, and having a positive impact on environmental management at the household level.